2017
DOI: 10.1007/s12672-017-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of 20-Hydroxyeicosatetraenoic Acid (20-HETE) in Androgen-Mediated Cell Viability in Prostate Cancer Cells

Abstract: 20-Hydroxyeicosatetraenoic acid (20-HETE) is generated intracellularly through the ω-hydroxylation of arachidonic acid by the cytochrome P450 (in humans, CYP4A11 and CYP4F2). 20-HETE induces mitogenic responses in different cancer cells. The aim of this study was to analyze how 20-HETE impacts cell survival, proliferation, and apoptosis in prostate cancer cells. Incubation of the human androgen-sensitive cells (LNCaP) with 1-10 μM HET0016 (a selective inhibitor of 20-HETE synthesis) reduced cell viability by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 54 publications
1
9
0
13
Order By: Relevance
“…Our laboratory has reported that 20-HETE production is key to sustain cell viability in an androgen sensitive prostate cancer cell line, primarily by prevention of apoptosis. These findings support a role for 20-HETE as a mediator in androgen driven prostate cancer cell survival [13]. Although prostate cancer tumor growth is initially dependent on androgens as documented by Huggins as early as 1941 [14], many patients eventually develop an androgen-insensitive more aggressive phenotype of prostate cancer, termed castrationresistant prostate cancer (CRPC).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our laboratory has reported that 20-HETE production is key to sustain cell viability in an androgen sensitive prostate cancer cell line, primarily by prevention of apoptosis. These findings support a role for 20-HETE as a mediator in androgen driven prostate cancer cell survival [13]. Although prostate cancer tumor growth is initially dependent on androgens as documented by Huggins as early as 1941 [14], many patients eventually develop an androgen-insensitive more aggressive phenotype of prostate cancer, termed castrationresistant prostate cancer (CRPC).…”
Section: Introductionsupporting
confidence: 58%
“…Cells were harvested in lysis buffer (Tris, 10 mM; NaCl, 150 mM; Triton X-100® 1%; EDTA, 1 mM; EGTA, 1 mM; Na 4 P 2 O 7 •10H 2 O, 10 mM; Na 3 VO 4 , 10 mM; and NaF, 100 mM) supplemented with a mix of protease inhibitors (cOmplete™ Mini EDTA-free, Roche Diagnostics, Mannheim Germany). Whole cell extracts for western blotting were prepared as described previously [13]. For subcellular fractionation, cell lysates were first centrifuged at 4°C for 7 min at 3100 xg.…”
Section: Cell Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the conclusion of the present study. In addition, many studies have confirmed that CYP4F2 was closely related to the metabolism of 20-hydroxyethyl hexadecanoic acid (20-HETE) [ 17 19 ]. In the past decade, 20-HETE has been recognized as a key conditioning agent of cancer progression, which can induce cell proliferation in vitro by stimulating the formation of reactive oxygen species and the production of vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the conclusion of the present study. In addition, many studies have con rmed that CYP4F2 was closely related to the metabolism of 20hydroxyethylhexadecanoic acid (20-HETE) (Stec, Roman et al 2007, Colombero, Papademetrio et al 2017. In the past decade, 20-HETE has been recognized as a key conditioning agent of cancer progression, which can induce cell proliferation in vitro by stimulating the formation of reactive oxygen species and the production of vascular endothelial growth factor.…”
Section: Discussionmentioning
confidence: 99%